Trend Detection of Drug Abuse Using Multivariate Analysis in Malaysia During the Years 2005 to 2015 - Arif Azizan, Izwan; Juahir, Hafizan; Ekhwan Toriman, Mohd; Mohamad, Mahadzirah; Abdullah, Norfazillah; Hanif Abdullah, Mohd (International Journal of Engineering and Technology, 2018)
This study aims to dismantling number drug abuser, cohort of age and drug type effects to improve our understanding of these trends and suggested groups for target intervention by stakeholders to effectively reduce resultant harms. Data of the study involving number of drug abuser, cohort of age (8 groups: < 13, 13-15, 16-19, 20-24, 25-29, 30-34, 35-39, > 40) and drug type was obtained by reviewing annual report of National Anti-Drug Agency (NADA) of Malaysia during 2009 to 2015. Descriptive statistics were applied to give distribution rate and patterns of the data. Cluster analysis then performed to grouped age cohort and drug type into homogenous clusters. Mann â€“ Kendall test were then applied at 5% interval level to identify any significant trends existed in all clusters. The result showed that age can be group into 3 clusters namely low-age cases, moderated-age cases and high-age cases, while for drug type 3 clusters were also created, low-drug type, moderate-drug type and high-drug type. Lastly, trend test shows that high-drug type (opiate) have very significant upward trend p < 0.05. Therefore, preventive strategies can be focus on young adult and opiate abused as it can greatly help reduce number of drug abuser in Malaysia.Â Â